Double anchoring squaraine dye with triazatruxene amine donor for dye-sensitized solar cells: sequential cosensitization for panchromatic light-harvesting - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
Dyes are firmly bound to a semiconducting TiO2 film using carboxylic acid anchoring groups for an efficient electron transfer from the excited state of dye to the conduction band (CB) of TiO2. Strong dye binding can be accomplished with multi-anchoring dye designs to improve photophysical characteristics, including high extinction coefficients, panchromatic absorption, post-sensitization modifications, and dark current suppression, besides enhancing the stability of the dye-TiO2 interface. Herein, a novel KV2D dye with double squaraine acceptor and double carboxylic acid anchoring groups is designed to achieve a high extinction coefficient (epsilon, 3.57 x 105M-1cm-1) and robust binding to the TiO2 film for an effective electron transfer. We systematically changed the amount of coadsorbent chenodeoxycholic acid (CDCA) to control the aggregation of dyes on the TiO2 surface that improves the power conversion efficiency (PCE, eta) for the devices based on the doubleanchoring KV2D. Out of these devices, KV2D: CDCA (1:10) based cell exhibited the best PCE of 5.26% with VOC of 754 mV, JSC of 10.41 mA/cm2, and ff of 67%. The sequential cosensitization studies were carried out with a far-red active dye to find the effect of the strong binding of the sensitizer to the TiO2 film. Interestingly, when di-anchoring, KV2D was sensitized first for 12 h and then sequentially cosensitized with far-red absorbing SQS4 for 5 h to achieve a PCE of 5.0% with VOC of 697 mV, JSC of 10.23 mA/cm2, and ff of 70% with panchromatic spectral response in IPCE upto 730 nm giving higher photocurrent generation.
Keywords: aggregation of dyes; Bulky donor unit; Double acceptor dye; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene

D-A-D based NIR and visible homodimeric squaraine dyes for dye-sensitized solar cells: Modulation of excitonic coupling - Siby, Jesna; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2026)
Dye-TiO2 interface plays a crucial role in the overall performance of dye-sensitized solar cells. Anchoring groups help to bind the dye on TiO2 and inject the electrons to the conduction band of TiO2. In this work, a series of homodimeric NIR squaraine dyes C6NIR, C10NIR, and visible squaraine dyes C6VIS, C10VIS are designed and synthesised. These dimeric dyes are covalently connected by decyl or hexyl units between the nonanchoring side of their monomeric unit. Optical spectroscopy in solution and on TiO2 surface indicates that the excitonic coupling between the dyes can be modulated. All the dimeric dyes showed better photovoltaic performance than their corresponding monomeric dyes. The dyes showed device performance SQ1 (1.28%) < C6NIR (2.26%) < C10NIR (2.79%) and AK2 (3.59%) < C6VIS (4.34%) < C10VIS (5.28%) respectively. The dimeric dyes showed better light harvesting efficiency and better passivation of the TiO2 surface. It helps to enhance the device's overall performance by improving the photocurrent and open circuit voltage. The decyl-linked dimeric dyes showed better performance among this set of dyes and C10NIR dyes showed V-oc of 614 mV, J(sc) of 7.08 mA/cm(2), and ff of 64.2%. and C10VIS showed V-oc of 724 mV, J(sc) of 10.74 mA/cm(2), and ff of 67.9%.
Keywords: charge recombination; Dye aggregation; Dye-sensitized solar cells; Dye-TiO2 interface; squaraine dyes; surface passivation